Андрей Блинов: о жизни и творчестве / А. Власенко - Власенко Александр Никитич (Удмуртия, 1986)
Экземпляры: Кр (1987) / Инвентарный номер: 11914 / Сис.шифр: 83.3(2Рос=Удм) / Авт.знак: В 58 / ГРНТИ: 17.01.09 / ББК: 83.3(2Рос=Удм)